Ionic liquids as powerful solvent media for improving catalytic performance of silyl borate catalyst to promote Diels-Alder reactions - Kumar, Anil; Pawar, Sanjay S. (Journal of Organic Chemistry, 2007)
[GRAPHICS] Use of the acidic chloroaluminate ionic liquid, including the recycled ones, can improve the catalytic activity of the toluene-coordinated silyl borate in enhancing rates, stereoselectivities, and yields of Diels-Alder reactions.